2015
DOI: 10.13189/ujer.2015.031112
|View full text |Cite
|
Sign up to set email alerts
|

Effective Foreign Language Teaching: Perceptions of Prospective English Language Teachers

Abstract: Studies conducted so far have mainly focused on investigating the characteristics of effective foreign language teachers to understand the role of teacher effectiveness in the process of language learning, while there is scarcity of studies focusing on the perceptions of the characteristics of effective foreign language teaching of the students of Department of English Language Teaching (ELT) and Department of English Language and Literature (EL&L) who are the major candidates of English language teaching prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…Numerous studies examining the characteristics of good and effective EFL teacher from the standpoint of a learner have been conducted to date (e.g., Barnes, 2013;Çakmak and Gündüz, 2018;Delaney, Johnson, Johnson, & Treslan, 2010;Demiroz & Yesilyurt, 2015;Febriyanti, 2018;Ghasemi & Hashemi, 2011;Javid, 2014;Kourieos & Evripidou, 2013;Lee, 2010;Mutlu & Özkan, 2017;Sabbah, 2018;Sandholtz, 2011;Zadeh, 2016).…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies examining the characteristics of good and effective EFL teacher from the standpoint of a learner have been conducted to date (e.g., Barnes, 2013;Çakmak and Gündüz, 2018;Delaney, Johnson, Johnson, & Treslan, 2010;Demiroz & Yesilyurt, 2015;Febriyanti, 2018;Ghasemi & Hashemi, 2011;Javid, 2014;Kourieos & Evripidou, 2013;Lee, 2010;Mutlu & Özkan, 2017;Sabbah, 2018;Sandholtz, 2011;Zadeh, 2016).…”
Section: Background Literaturementioning
confidence: 99%
“…For instance, the study by Demiroz and Yesilyurt (2015) aimed at examining how prospective English teachers at two English language departments in Turkey (Department of English Language Teaching and Department of English Language and Literature) perceive effective foreign language teachers. The findings indicated that statistically significant differences exist between the two groups in favor of the English language teaching department.…”
Section: Background Literaturementioning
confidence: 99%
“…A large body of research has been published which has contrasted views of students with teachers (e.g., Brosh 1996;Brown, 2009), native and non-native teachers (e.g., Borean & Incecay, 2018) and pre-service and in-service teachers (e.g., Borean & Incecay, 2018). Recent studies have also reflected on different countries and learning/teaching contexts and reported data from Turkish (Çelik, Arikan, & Caner, 2013;Demiroz, H., & Yesilyurt, 2015;Göksel & Rakicioglu-Söylemez, 2018)…”
Section: Characteristics Of the Effective Language Teachermentioning
confidence: 99%
“…Various studies on the attributes of an effective English language teacher have been conducted in numerous contexts including in Turkey (Wong 2000;Borg 2006;Cheung 2006;Malikow 2006;Park & Lee 2006;Arıkan, Taser & Saraç-Süzer 2008;Arıkan 2010;Çubukçu 2010;Wichadee 2010;Ghasemi & Hashemi 2011;Kourieos & Evripidou 2013;Demiröz & Yeşilyurt 2015;Baytur & Razı 2015). The results of these and similar studies have shown that perceptions of effectiveness display both similarities and differences in particular contexts.…”
Section: The Significance Of the Studymentioning
confidence: 99%
“…The study by Çelik, Arıkan, and Caner (2013) with 998 Turkish undergraduates concluded that being fair and just, showing enthusiasm, friendliness, being loving, creativity, being experienced, and being humorous were reported as the qualities of an effective language teacher. Demiröz and Yeşilyurt (2015) in their study of prospective English language teachers revealed that an effective language teacher should teach communicatively and indirectly correct students' mistakes.…”
Section: Studies On Learners' Perceptions Of Effective Language Teachmentioning
confidence: 99%